Motivasi Remaja Menggunakan Hijab: Studi pada Remaja Desa Kebon IX Sungai Gelam, Muaro Jambi - Dewi Sumarni; Arfan Arfan (Prodi Bimbingan dan Konseling Islam (BPI) Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2021)
The motivation for wearing the hijab in Islam is a form of spiritual education effort that forms in itself a religious awareness or as a need for an integrated attitude of belief and values. Motivation has the meaning of encouragement, reason, or purpose of action. The use of the headscarf is a form of religious behavior and the result of a Muslim motivation. This study aims to determine: first, what are the types of religious motivations of adolescents in Kebon IX Village; second, what are the factors that influence the religious behavior of adolescents; and third, what is the motivation of teenagers to wear the hijab. This study uses a qualitative method, with an approach to Psychology of Religion. The sources of data in this study are data from observations for 30 days in March 2021 and interviews with 20 sources, accompanied by the collection of documents needed by researchers to find and explore more comprehensive information. The results of the study found that: first, the types of religious motivation of adolescents in Kebon IX Village consisted of intrinsic and extrinsic, while Islamically the religious motivations of adolescents in Kebon IX Village consisted of jismiyyah, Nafsiyah, and Ruhiyyah motivations; Second, the factors that influence the religious behavior of adolescents are the presence of internal and external factors; and third, the motivation of teenagers to wear the hijab is because of their self-awareness that wearing the hijab is an obligation for all Muslim women, and there are also teenagers who wear the hijab because of the motivation and encouragement from outside the individual, namely from family and environmental encouragement. This study also found that adolescent religious motivation greatly influences adolescent religious behavior, such as wearing the hijab, praying, fasting, reading the Koran, and having an attitude of helping, respecting each other, having noble character, etc. The theoretical implication of this research is to prove the theory of Jalaluddin Rahmat's religious motivation. Practically it will become a socio-religious document for the people of Kebon IX Village, Sungai Gelam District, Muaro Jambi Regency.